COVID-19 may lower quality of life when infections and deaths increase: A longitudinal study in the Peruvian jungle - Moya-Salazar, Jeel (2023)
“Background: Quality of life (QoL) is a multifactorial concept on the perception of the individual’s wellbeing underpinned by environmental, psychological, and physical factors. Several studies have shown changes in QoL in the COVID-19 pandemic and may be due to increases in mortality rates, however, no study has investigated this among Peruvian jungle dwellers. Here, we have sought to estimate the QoL of individuals before and after the increase in cases and deaths from COVID-19. Methods: A questionnaire-based longitudinal study was conducted in 102 inhabitants (mean 40.75 ± 7.49 years). The Spanish version of the WHOQOL-BREF was used in two stages: April and June. The first stage was accomplished before the first confirmed case of COVID-19, and the second stage was when the daily mortality rate was 3.5% with an incidence of 87%. Results: Sixty (54.8%) participants were women, 67 (61.9%) were >31 years, and 38 (34.5%) and 32 (29.1%) participants had primary and secondary education, respectively. In the first and second stage we obtained an overall mean QoL of 46.65 ± 23.2 and 35 ± 27.7 points, respectively. Individuals had significantly lower QoL in the face of increased deaths in physical (p = 0.001), mental (p = 0.028) and environmental (p = 0.001) health domains, with the latter having the greatest impact (51.84 ± 5.81 vs. 16.66 ± 5.55 points). Conclusion: Quality of life of Peruvian jungle dwellers is reduced during periods of increased mortality and incidence by COVID-19. Preventive strategies aimed at reducing the impact of COVID-19 on the mental health and global wellbeing of individuals living in the Amazon are recommended to Peruvian authorities.“